Enhancing Primary Care Experiences for Homeless Patients with Serious Mental Illness: Results from a National Survey. (February 2021) - Gabrielian, Sonya; Jones, Audrey L.; Hoge, April E.; deRussy, Aerin J.; Kim, Young-il; Montgomery, Ann Elizabeth; Blosnich, John R.; Gordon, Adam J.; Gelberg, Lillian; Austin, Erika L.; Pollio, David; Holmes, Sally K.; et al.
Objectives: Patients experiencing homelessness (PEH) with serious mental illness (SMI) have poor satisfaction with primary care. We assessed if primary care teams tailored for homeless patients (Homeless-Patient Aligned Care Teams (H-PACTs)) provide this population with superior experiences than mainstream primary care and explored whether integrated behavioral health and social services were associated with favorable experiences. Methods: We surveyed VA PEH with SMI (n = 1095) to capture the valence of their primary care experiences in 4 domains (Access/Coordination, Patient-Clinician Relationships, Cooperation, and Homeless-Specific Needs). We surveyed clinicians (n = 52) from 29 H-PACTs to elucidate if their clinics had embedded mental health, addiction, social work, and/or housing services. We counted these services in each H-PACT (0-4) and classified H-PACTs as having high (3-4) versus low (0-2) service integration. We controlled for demographics, housing history, and needs in comparing H-PACT versus mainstream experiences; and experiences in high versus low integration H-PACTs. Results: Among respondents, 969 (91%) had complete data and 626 (62%) were in H-PACTs. After covariate adjustment, compared to mainstream respondents, H-PACT respondents were more likely ( P < .01) to report favorable experiences (AORs = 1.7-2.1) and less likely to report unfavorable experiences (AORs = 0.5-0.6) in all 4 domains. Of 29 H-PACTs, 27.6% had high integration. High integration H-PACT respondents were twice as likely as low integration H-PACT respondents to report favorable access/coordination experiences (AOR = 1.7). Conclusions: Homeless-tailored clinics with highly-integrated services were associated with better care experiences among PEH with SMI. These observational data suggest that tailored primary care with integrated services may improve care perceptions among complex patients.